The relationship among emotional intelligence, psychological maladjustment and behavior problems during adolescence - Hafızoğlu, Şengül. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2007., 2007)
The aim of the current study was to investigate the relationship among emotional intelligence, psychological adjustment/ maladjustment and teacherreported behavior problems of adolescents between ages 16 and 17 years. There were 84 adolescents (41 females, 43 males). The study also looked at the possible predictors of behavior problems. Emotional intelligence was measured by Bar-On Emotional Quotient Inventory, Bar-On EQ-i (Bar-On, 1997), psychological adjustment/ maladjustment was measured by Personality Adjustment Questionnaire, PAQ (Rohner, 1971) and behavior problems was measured by Conners’ Teachers’ Rating Scale CTRS-28 (Conners, 1969). Results of the study displayed that there was a significant negative correlation between emotional intelligence and behavior problems (r= -.25, p<.05). However the relationship between emotional intelligence and psychological adjustment, and psychological adjustment and behavior problems were not statistically significant. Intercorrelations among subtests of emotional intelligence (measured by Bar-On EQ-i) and subtests of psychological adjustment/ maladjustment (measured by PAQ) revealed significant results as well. Stepwise regression analysis showed that GPA was the strongest predictor of behavior problems, followed by interpersonal relationships subtest of Bar-On EQ-i, self regard subtest of Bar-On EQ-i and optimism subtest of Bar-On EQ-i. iv Referring to the significant negative relationship between emotional intelligence and behavior problems, the study results may be utilized in emphasizing emotional literacy and emotional intelligence in the school curriculum. Those students with higher scores in emotional intelligence are better in understanding their feelings and others’ feelings, better in interpersonal relationships, in dealing with problem situations and in controlling their impulses (Golemen,1995). Counselors and school psychologists may focus on emotional intelligence in their counseling programs to reduce the prevalence of behavior problems and to foster good interpersonal relationships, emphatic skills and effective problem solving abilities.
Keywords: Emotional intelligence.; Adjustment (Psychology) in adolescence.; Behavior disorders in adolescence